2020
DOI: 10.3390/life10120356
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Genomics, Phylogenomics and Proteomics Approaches in Ascomycota

Abstract: Fungi are among the most successful eukaryotes on Earth: they have evolved strategies to survive in the most diverse environments and stressful conditions and have been selected and exploited for multiple aims by humans. The characteristic features intrinsic of Fungi have required evolutionary changes and adaptations at deep molecular levels. Omics approaches, nowadays including genomics, metagenomics, phylogenomics, transcriptomics, metabolomics, and proteomics have enormously advanced the way to understand f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 412 publications
(630 reference statements)
1
9
0
Order By: Relevance
“…They can adapt to a wide range of substrates in challenging environments such as ultraviolet light, water and high temperature stress [ 23 ]. Ascomycota has been shown to be pathogenic fungi in plants and insects [ 24 ]. However, Mycosphaerella was dominant in non-bagging group at the beginning of the storage period which was significantly different from the bagging group.…”
Section: Discussionmentioning
confidence: 99%
“…They can adapt to a wide range of substrates in challenging environments such as ultraviolet light, water and high temperature stress [ 23 ]. Ascomycota has been shown to be pathogenic fungi in plants and insects [ 24 ]. However, Mycosphaerella was dominant in non-bagging group at the beginning of the storage period which was significantly different from the bagging group.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when compared to the control, it was observed that B4-7 significantly increased the abundance of Firmicutes and Mortierellomycota, while significantly reducing the abundance of Ascomycota and Basidiomycota. Additionally, studies have indicated that Ascomycota and Basidiomycota are known to include plant and insect pathogenic fungi ( Muggia et al., 2020 ). Mortierellomycota contributes to the decomposition of organic matter and cellulose in soil, providing nutrients for plant growth ( Purahong et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of microorganisms to survive and proliferate in extreme environments is facilitated by numerous characteristics; chief among them is their capacity to withstand the competition and stress presented by their natural habitats 1 , 2 . These microorganisms are capable of adapting to both physical and chemical stressors via phenotypic plasticity 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%